C-reactive protein concentrations are higher in dogs with stage IV chronic kidney disease treated with intermittent hemodialysis. - Maria Gabriela Picelli de Azevedo; Silvano Salgueiro Geraldes; Paula Bilbau Sant'Anna; Beatriz Poloni Batista; Suellen Rodrigues Maia; Reiner Silveira de Moraes; Elizabeth Moreira Dos Santos Schmidt; Fabiana Ferreira de Souza; Alessandra Melchert; João Carlos Pinheiro Ferreira; Carmel Rezende Dadalto; Henry David Mogollón García; et al. (PLoS ONE, 2022)
In chronic kidney disease dogs, the inflammatory process increases C-reactive protein concentrations. This study aimed to determine C-reactive protein serum concentrations in stage IV chronic kidney disease dogs treated with intermittent hemodialysis. A prospective cohort study was conducted with 23 dogs allocated into three groups: control group (CG, n = 7), intermittent hemodialysis group (IHG, n = 8) and clinical treatment group (CTG, n = 8), both comprised of stage IV chronic kidney disease dogs. One blood sample from CG (initial evaluation) and two samples from IHG and CTG (first- and last-moment) were obtained to determine C-reactive protein concentration, total leukocytes, platelets, erythrocytes, total plasma protein, serum albumin, urea, creatinine, and phosphorus. C-reactive protein was higher in IHG compared to CG in the first- and last-moments (p <0.001) and compared to CTG in the first-moment (p = 0.0406). C-reactive protein presented moderate positive correlation with leukocytes (r = 0.5479; p = 0.01), and moderate negative correlation with albumin (r = - 0.5974; p = 0.006) and red blood cells (r = - 0.5878, p = 0.01). A high correlation coefficient was observed in the tests' evaluation (CI = 0.59-0.78; r = 0.70; P<0.0001). In conclusion, both assays used in this study to measure C-reactive protein have provided safe and reliable quantification of the results. Additionally, despite IHG dogs presented an active inflammatory profile, intermittent hemodialysis has proven to be beneficial, leading to a clinical improvement in life quality of patients, and thus being recommended for stage IV CKD dogs when performed by trained professionals.